CTA Characteristics of the Circle of Willis and Intracranial Aneurysm in a Chinese Crowd with Family History of Stroke. (4th January 2016) - Jin, Zhang-ning; Dong, Wen-tao; Cai, Xin-wang; Zhang, Zhen; Zhang, Li-tong; Gao, Feng; Kang, Xiao-kui; Li, Jia; Wang, Hai-ning; Gao, Nan-nan; Ning, Xian-jia; Tu, Jun; et al.
Abstract : Background and Purpose. The vascular morphology in crowd with family history of stroke remains unclear. The present study clarified the characteristics of the intracranial vascular CoW and prevalence of intracranial aneurysms in subjects with family history of stroke. Methods. A stratified cluster, random sampling method was used for subjects with family history of stroke among rural residents in Jixian, Tianjin, China. All the subjects underwent a physical examination, head computed tomography (CT) scan, and cephalic and cervical computed tomography angiography (CTA) scan. Anatomic variations in the Circle of Willis and cerebrovascular disease in this population were analyzed. Results. In the crowd with similar living environment, stable genetic background, and family history of stroke and without obvious nerve function impairment (1) hypoplasia or absence of A1 segment was significantly different in gender (male versus female: 9.8% versus 18.8%, p = 0.031 ), especially the right-side A1 (male versus female: 5.9% versus 16.4%, p = 0.00 4 ). (2) Hypoplasia or absence of bilateral posterior communicating arteries was more common in men than women (58.2% versus 45.3%, p = 0.032 ). Unilateral fetal posterior cerebral artery was observed more often in women than men (17.2% versus 8.5%, p = 0.028 ). (3) The percentage of subjects with incomplete CoW did not increase significantly with age. Compared to healthy Chinese people, the crowd had a higher percentage of incomplete CoW (p < 0.00 1 ). (4) No obvious correlation between risk factors and CoW was found. (5) The prevalence of aneurysm was 10.3% in the special crowd. Conclusions. The certain variations of CoW showed significant relation to gender, but not to age in people with family history of stroke. The incomplete circle may be a dangerous factor that is independent of common risk factors for stroke and tend to lead to cerebral ischemia in the crowd with family history of stroke. The prevalence of intracranial aneurysm is comparatively high in the present subjects compared to other people.